2002
DOI: 10.1039/b110839p
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical reactions at the n-GaN electrode in 1 M H2SO4 and in acidic solutions containing Cl– ions

Abstract: The photoelectrochemical behaviour of n-GaN in contact with 1 M H 2 SO 4 and with acidic solutions containing Cl À ions was studied using rotating-ring-disk voltammetry, electrochemical impedance spectroscopy and etching experiments. It was found that n-GaN is stabilized against photoanodic decomposition in the presence of Cl À ions due to the competing oxidation of Cl À to Cl 2 . The competition kinetics were interpreted on the basis of a mechanism, in which intrinsic surface states take part in the photoanod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 9 publications
1
30
0
Order By: Relevance
“…In 1 M H 2 SO 4 , however, we have previously shown that the photocurrent is completely associated with the etching of the semiconductor material [1]. From the experimental relationship between DI D /|DI R | and the photocurrent DI D for different Cl --concentrations, we were able to deduce [4] that the most probable mechanism for the photooxidation of Cl --at n-GaN in competition with the photoanodic dissolution involves intrinsic surface states S,…”
Section: Discussionmentioning
confidence: 96%
“…In 1 M H 2 SO 4 , however, we have previously shown that the photocurrent is completely associated with the etching of the semiconductor material [1]. From the experimental relationship between DI D /|DI R | and the photocurrent DI D for different Cl --concentrations, we were able to deduce [4] that the most probable mechanism for the photooxidation of Cl --at n-GaN in competition with the photoanodic dissolution involves intrinsic surface states S,…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, Huygens [20] found that a Cl À concentration as high as 1.2 M does not supply enough Cl À ions at the solid -liquid interface to completely suppress the oxidation of the GaN surface. Excess holes in the GaN valence band participate in the anodic etching of the GaN surface, which in acidic solutions proceeds according to the following overall oxidation reaction:…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…Anodic dissolution of a GaN electrode is, however, a problem for achieving stable photoelectrolysis. Although the dissolution is prevented by using Cl contained solutions like HCl, the electochemical reaction at the GaN surface is the Cl-ion oxidation instead of oxygen generation from water [4,5]. Investigation of photoelectrochemical reactions are important in order to achieve stable water splitting by n-type GaN.…”
mentioning
confidence: 99%